PENGETAHUAN, SIKAP DAN PRAKTIK PENGGUNAAN OBAT ANTIDIABETES SECARA KONVENSIONAL DAN KOMPLEMENTER PADA PASIEN DIABETES DI RUMAH SAKIT X KOTA MALANG - Rhima Diastya Amalia; Aditama, Lisa; Rahem, Abdul (Jurnal Insan Farmasi Indonesia, 2025)
The long term diabetes mellitus treatment, encouraging patients to try alternative medicine. The Knowledge, Attitude and Practice Study has been used to determine the ability of patients in use of alternative and complementary medicine. This study aims to determine the differences in sociodemographic characteristics, knowledge, attitudes and practices between Type 2 Diabetes Mellitus (T2DM) patients who consume complementary herbal medicine and T2DM patients who consume conventional medicine. The design of this study, non-experimental cross-sectional, was conducted in August 2024 at a Hospital in Malang City. The number of respondents was 105 patients with a diagnosis of T2DM. Data were collected using questionnaires filled out independently by the patients. Data analysis used SPSS 30. The results showed no differences in sociodemographics and clinical between the two groups (p≥0,05). The knowledge of patients who use complementary herbal medicine showed more positive results, they have knowledge to not to stop conventional drugs prescribed by doctors (p=0,030). However, they have a more negative attitude in terms of choosing not to discuss with a doctor before using complementary herbal medicine (p=0,007). In practice there was a significant difference between the two groups (p < 0,001).